Variations in Organization Science : In Honor of Donald T. Campbell. - Baum, Joel A. C. A. C. (SAGE Publications, 1999)
Variations in Organization Science celebrates Donald T Campbell's many contributions to organization science, presenting new variations which stem directly from his work. Contributing authors review and extend Campbell's theories in four major areas: blind variation, selection and retention especially inside firms; multilevel co-evolution in organizational parts and wholes; process level analysis and modeling epistemology and methodology. The book includes an unusual appendix, Donald T Campbell's curriculum vitae.